The Use of Waste Utilization Learning Videos on Learning Outcomes of Elementary School Students - Dila Nurul Fadilah; Asep Bayu Dani Nandiyanto (Research and Social Study Institute, 2022)
This study aims to analyze the teaching of waste utilization starting from the definition, type, processing process as well as the use of waste using digital learning methods for elementary school students. The study was conducted on 30 elementary school students in Bekasi City, Indonesia. Learning using video media through google meet. This data collection analysis used pre-test and post-test questions as many as 20 questions. Final score pretest and posttest the application of the media were compare with the test (Paired Sample t-Test) via SPSS 25 for windows. The result of this research is that there is an increase in learning outcomes regarding the use of waste after students watch the video and it is also explained through google meet. It can be seen that there is an increase from 37,586 to 85,571 in the post-test from the pre-test average results. the value of sig (2-tailed) 0,000 < 0,05. This indicates that there is a significant influence on the use of learning video media on waste utilization on the learning outcomes of elementary school students.